Memórias docentes: percepção e valoração de um tempo/espaço pretérito - Ivan Fortunato; Solange Terezinha de Lima-Guimarães (EccoS – Revista Científica)
In this social status that is marked by several and simultaneous crises, Guattari's ecosophy emerges as a potential instrument to cope with the relational, ecological and axiological wearing caused by this multi-critical scenario. In this research, the mental ecology in/from the everyday school is put in motion from the bio:graphy of teachers with long experience in narratives of life history, like indicated by Eclea Bosi. By sharing their own experiences, individuals can understand themselves as authors of their own history. This movement allows to see and to value the education as a territory of possible transformation of subjectivities and social relations. Valorizing that carries a positive valence in axiological recovery for a society permeated by vivacity in relations.